Impact of workplace violence and compassionate behaviour in hospitals on stress, sleep quality and subjective health status among Chinese nurses: a cross-sectional survey. Issue 10 (3rd October 2018) - Zhang, Shu-E; Liu, Wenhui; Wang, Jinghui; Shi, Yu; Xie, Fengzhe; Cang, Shuang; Sun, Tao; Fan, Lihua
Abstract : Objectives: The aim of this study is to describe the current state of workplace violence (WPV) and compassionate behaviour towards nurses and to explain how they affect nurses' stress, sleep quality and subjective health status. Design: A cross-sectional online survey study. Setting: The survey was conducted across eight provinces in China. Participants: A total of 1024 nurses were recruited to complete an online questionnaire survey from February to May 2016 in China. Results: Approximately 75.4% participants had experienced some form of violence. Most of the participants experienced WPV such as verbal violence (65.2%), made difficulties (54.5%), tarnished reputation (37.5%), mob behaviour (34.9%), intimidation behaviour (18.8%), physical violence (14.6%) and sexual harassment (5.9%). In this study, 92.4% participants experienced compassionate behaviour from their coworkers (84.9%), supervisors (67.3%), and from their patients (65.3%). The results show that the exposure to WPV behaviour significantly affected the psychological stress (β=0.295, p<0.01), sleep quality (β=−0.198, p<0.01) and subjective health status (β=−0.252, p<0.01) of nurses. The exposure to compassionate behaviour significantly affected the psychological stress (β=−0.229, p<0.01), sleep quality (β=0.326, p<0.01) and subjective health status (β=0.342, p<0.01) of nurses. The results of the mediation analysis showed that psychological stress is a partial mediator in the relationship between violence and sleep quality (β=−0.458, p<0.01) and between violence and subjective health (β=−0.425, p<0.01). Moreover, psychological stress also partially mediated the relationship between compassionate behaviour and sleep quality (β=−0.473, p<0.01), and between compassionate behaviour and subjective health (β=−0.405, p<0.01). Conclusion: In China, most nurses have experienced different forms of WPV from patients and/or their relatives, as well as experiencing various forms of compassionate behaviour from their coworkers, supervisors and/or patients. This study investigates the prevalence of the different types of WPV and compassionate behaviour. Several aspects of harm to nurses from exposure to violence is confirmed. We found that WPV can damage nurses' health outcomes, while compassionate behaviours were beneficial to their health outcomes. A harmonious nursing environment should be provided to minimise threats to nurses' health status.